The Problems of Development and Economic Security in Yemen - Al-Aghbari, Areeg Gamil; Nugroho, Rino Ardhian; Kartono, Drajat Tri (Proceedings of Sunan Ampel International Conference of Political and Social Sciences, 2024)
This review article investigates and examines the obstacles and critical challenges to Yemen's development and economic security, focusing on the consequences of protracted conflict, hyperinflation, and inadequate government. The study employs a qualitative research methodology, synthesizing insights from scholarly literature, reports from international organizations, and case studies to explore the complex dynamics at play. Data was gathered by doing focused searches using keywords like “problems,” “development,” “economic security,” “stabilization,” and “Yemen” on websites including Google Scholar, ScienceDirect, and Scopus. This comprehensive analysis aims to provide a nuanced understanding of Yemen’s current economic landscape and the factors contributing to its decline. Results reveal that Yemen's protracted conflict has seriously harmed the country's economic framework, resulting in pervasive poverty, unstable food supplies, and a breakdown of social services. Corruption and inept governance have exacerbated these problems, impeding efforts to stabilize the economy and restore public trust. The impact of large international help is still limited because of continued violence and logistical obstacles in the delivery of relief. According to the study's findings, Yemen's recovery would necessitate a multimodal strategy that includes investments in education and career training, currency stabilization, economic diversification, and governance reforms. Effective governance and ongoing international support are also critical to achieving sustainable development and long-term stability.